A escolarização da linguagem visual: uma leitura dos documentos ao professor - Ronan Cardozo Couto (2000)
This dissertation aimed to discuss the schooling of visual language, analyzing its insertion in teaching materials and in the official discourse that guides fundamental education, as well as its theoretical basis. In knowledge building, vision, influenced by culture and by the personal and social historical moment, is not only spontaneous: reasoning and feeling are reflected on it. The corpus analyzed was the national curricular parameters of fundamental (Parâmetros Curriculares Nacional: Ensino Fundamental), specially the national curricular parameters of fundamental education/arts (Parâmetros Curriculares Nacionais: ensino fundamental/Arte) published in 1997 and 1998, the textbooks A Arte de Fazer Arte (1999) and Aprendendo Arte (2000). In order to understand the way visual language is presented in such documents, the themes related to this subject are emphasized in the analysis. The author establishes a relationship between the theoretical approach and the schooling of visual language as proposed in documents written to art teachers. The research on visual language and the insertion of this knowledge in fundamental education build this research and suggest the reflection upon new knowledge, in the moment that art teaching methods emphasize the reading and appreciation of visual image as one of its important specific contents.